RESPON APLIKASI ASAM HUMAT DAN NITROGEN TERHADAP HASIL, DAN KUALITAS UMBI BAWANG MERAH (Allium ascalonicum L.) - Yuniarti, Ananda Rahmalia; Suciaty, Tety; Budirokhman, Dodi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2025)
This research aims to determine (1) Interaction of humic acid and nitrogen application on growth, yield, and quality of shallot (2) To determine the effect of the combination of nitrogen fertilizer and humic acid and determining the right dose for yield, and quality of shallot. This research was conducted in Kuningan which is located in Lengkong Village, Garawangi District, Kuningan Regency, West Java Province. The research location has an altitude of 600 meters above sea level, average temperature of 180C to 320C, and an average rainfall of 1,433.6 mm/year. This research was conducted from November 2023 to January 2024. The method used is the experimental method with a Randomized Group Design (RAD) factorial pattern. The treatment consisted of 2 factors, the dose of humic acid and the dose of nitrogen fertilizer. The dose of humic acid consisted of four levels: A0 = Control (Without Humic Acid), A1 = 2 kg / ha, A2 = 4 kg / ha, and A3 = 6 kg / ha. While the treatment of nitrogen fertilizer dose consisted of four levels: N1 = 25% of the recommended dose (urea 62.5 kg / ha), N2 = 50% of the recommended dose (urea 125 kg / ha), N3 = 75% of the recommended dose (urea 187.5 kg / ha), N4 = 100% of the recommended dose (urea 250 kg/ha). From these two factors, 16 treatment combinations were obtained and repeated 2 times, so that overall there were 32 experimental plots, in each experimental plot 5 plants were selected as sample plants. Based on the results of the research and discussion, the following conclusions are: 1 (a) The dose of humic acid and nitrogen fertilizer gave a significant interaction effect on variables of root crown ratio, bulb volume, fresh bulb weight/plant, fresh bulb weight per plot, sun-dried tuber weight per clump, sun-dried tuber weight/plot, bulb weight loss and bulb dissolved solids. (b) Humic acid gave a significant effect on all variables, except for weight loss and water content. The dose of nitrogen fertilizer gave a significant effect on all observation variables except for the water content observation variable. 2. The humic acid dose of 6 kg/ha had the best effect on the growth component. The humic acid dose of 4 kg/ha and nitrogen 187.5 kg/ha gave the best effect on the weight of sun-dried bulb per plot of 1.78 kg or equivalent to 8.43 tons/ha.